Solving Hayashi and Prescott (2007) "The 1990s: Japan's Lost Decade"(extended with an exogenous population growth and labour-augmenting technical progress) using a Linear-Quadratic Approximation as in Ljungqvist and Sargent (2004) - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2009)
This notes outlines how to solve Hayashi and Prescott (2007) "The 1990s: Japan's Lost Decade", extended with an exogenous population growth and labour-augmenting technical progress, using a Linear-Quadratic Approximation as in Ljungqvist and Sargent (2004).
Keywords: 330